2015
DOI: 10.2188/jea.je20140176
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Amyotrophic Lateral Sclerosis in Patients With Diabetes: A Nationwide Population-Based Cohort Study

Abstract: BackgroundGlucose intolerance in patients with amyotrophic lateral sclerosis (ALS) has been inconsistently reported. Evidence for the association of ALS and diabetes mellitus is limited. We aimed to assess the overall and age- and sex-specific risks of ALS among patients with diabetes in Taiwan.MethodsThe study cohort included 615 492 diabetic patients and 614 835 age- and sex-matched subjects as a comparison cohort, followed from 2000 to 2008. We estimated the incidence densities of ALS and calculated the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…The statistically significant increase in the risk of ALS before age 50 amongst individuals with insulin-dependent diabetes was based on eight cases and seven controls with insulin-dependent diabetes. However, in the study by Sun et al [4] men aged ≤65 years showed the most increased hazard ratio (HR) of ALS for diabetes (1.67, 95% CI 1.18-2.36), consistent with the HR of ALS before age 65 amongst men in our study (1.70, 95% CI 0.98-2.96, 17 cases and 50 controls with diabetes). The literature suggests that young-onset diabetes may be associated with increased ALS risk and further research on the role of type 1 diabetes in ALS is warranted.…”
supporting
confidence: 91%
“…The statistically significant increase in the risk of ALS before age 50 amongst individuals with insulin-dependent diabetes was based on eight cases and seven controls with insulin-dependent diabetes. However, in the study by Sun et al [4] men aged ≤65 years showed the most increased hazard ratio (HR) of ALS for diabetes (1.67, 95% CI 1.18-2.36), consistent with the HR of ALS before age 65 amongst men in our study (1.70, 95% CI 0.98-2.96, 17 cases and 50 controls with diabetes). The literature suggests that young-onset diabetes may be associated with increased ALS risk and further research on the role of type 1 diabetes in ALS is warranted.…”
supporting
confidence: 91%
“…However, the incidence of abnormal glucose tolerance tests in ALS patients ranges from 19-72% [9,113,115,116,117,118], and therefore subtle alterations in glucose handling could occur in ALS. Abnormal glucose metabolism does not appear to affect survival or disease severity [114,119]; however, one Taiwanese study reported an increased risk of ALS in those with DM [120]. By contrast, a Danish study found that type 2 DM is protective for ALS [121], and individuals with DM have been found to have an average of 4 years later onset of ALS than those without DM [122].…”
Section: Meeting Energy Needs In Alsmentioning
confidence: 99%
“…A recent systematic review also revealed that ALS was associated with diabetes mellitus (Lekoubou et al, 2014). However, whether there is a causal relationship between glucose homeostasis abnormalities and ALS is controversial (Sun et al, 2015). Moreover, two antidiabetic drugs, metformin and pioglitazone, seem to have no beneficial effect in the SOD1 G93A mouse model of ALS (Kaneb et al, 2011) and a clinical trial (Dupuis et al, 2012;Jawaid et al, 2014).…”
Section: Alsmentioning
confidence: 99%